2022
DOI: 10.1128/spectrum.02419-21
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of BET Family Proteins Suppresses African Swine Fever Virus Infection

Abstract: Due to the continuing spread of the ASFV in the world and the lack of commercial vaccines, the development of improved control strategies, including antiviral drugs, is urgently needed. BRD4 is an important epigenetic factor and has been commonly used for drug development for tumor treatment.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…BRD2 is reported to interact with many chromatin- and transcriptional activation-related proteins to regulate the transcription of diverse genes [ 32 , 33 , 34 ]. Importantly, several studies have shown that viruses hijacking BRD2 to enhance viral gene transcription is beneficial for viral replication [ 22 , 23 , 35 , 36 ]. Consistent with these findings, we previously found that the expression level of chBRD2 was obviously reduced in both NDV-infected cells and pEGFP-M-transfected cells, which facilitated vRNA synthesis and transcription [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BRD2 is reported to interact with many chromatin- and transcriptional activation-related proteins to regulate the transcription of diverse genes [ 32 , 33 , 34 ]. Importantly, several studies have shown that viruses hijacking BRD2 to enhance viral gene transcription is beneficial for viral replication [ 22 , 23 , 35 , 36 ]. Consistent with these findings, we previously found that the expression level of chBRD2 was obviously reduced in both NDV-infected cells and pEGFP-M-transfected cells, which facilitated vRNA synthesis and transcription [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ]. In recent years, BRD2 has also been found to participate in the replication of multiple DNA or RNA viruses via interacting with viral proteins [ 21 , 22 , 23 , 24 ]. In our previous studies, we demonstrated that chicken BRD2 (chBRD2) was a novel interacting partner of NDV M protein [ 9 ], and the C-terminus (aa 264–313) of M protein was responsible for direct interaction with the extra-terminal (ET) domain (aa 619–683) of chBRD2 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The bromodomain terminal (BET) family of proteins, including BRD2, BRD3, BRD4 and BRDT, are epigenetic readers of gene transcriptional regulation ( 54 ). Bromo dopamine-containing protein 4 (BRD4) is the most studied member of the BET family, which interprets the epigenetic code by binding to acetylated histones and non-histones, regulating a variety of cellular processes including cell cycle, cell differentiation and cell proliferation ( 55 ).…”
Section: Synergistic or Accelerating Roles Of Cirrhosis In The Mechan...mentioning
confidence: 99%